Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1159/000489813
|View full text |Cite
|
Sign up to set email alerts
|

Stapes Surgery for Otosclerosis in Patients Presenting with Mixed Hearing Loss

Abstract: Objectives: To evaluate the efficacy of stapes surgery in patients presenting with a preoperative mixed hearing loss (bone conduction thresholds ≥40 dB; 40 < air conduction thresholds (AC) < 85 dB). Patients and Methods: A total of 30 patients (32 ears) with mixed hearing loss who underwent primary stapedotomy were evaluated. Audiometric parameters were assessed before and after surgery. Contralateral thresholds were also reported. The need for a hearing aid (HA) after surgery and its impact on quality of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The resemblance to otosclerosis was primarily due to the presence of progressive hearing loss and absent stapedial reflexes in all three patients. Additionally, the mixed hearing loss observed in these patients further complicated the clinical picture, as otosclerosis can also present with mixed hearing loss in advanced stages [ 1 , 17 ]. In a case report published by Távora-Vieira and Miller in 2012, the authors reported that the misdiagnosis and mismanagement of a case of EVA syndrome led to profound hearing loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The resemblance to otosclerosis was primarily due to the presence of progressive hearing loss and absent stapedial reflexes in all three patients. Additionally, the mixed hearing loss observed in these patients further complicated the clinical picture, as otosclerosis can also present with mixed hearing loss in advanced stages [ 1 , 17 ]. In a case report published by Távora-Vieira and Miller in 2012, the authors reported that the misdiagnosis and mismanagement of a case of EVA syndrome led to profound hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of acoustic reflexes, VEMP responses, and distortion product otoacoustic emissions (DPOAEs) in some cases further argued against middle-ear disease. CT scans were crucial in the differential diagnosis, showing large vestibular aqueducts in the affected ears without stapedial footplate alterations, which are typically seen in otosclerosis [ 10 , 17 , 18 , 19 ]. As emerges from the cited literature, atypical cases of EVA and otosclerosis can pose a significative diagnostic challenge due to the possibility of overlapping clinical and audiological features (ABGs at low frequencies, same state of stapedial reflexes, and normal middle-ear function), making differential diagnosis challenging [ 1 , 2 , 4 , 5 , 10 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For more than 50 years, treatment of this form of hearing loss relied first on stapedectomy and more recently on stapedotomy (6). High rates of success of otosclerosis treatment using stapes surgery, with long-term stable outcomes, have been demonstrated repeatedly in many studies (7,8). Pure-tone audiometry is the "gold standard" in assessing the effectiveness of stapes surgery.…”
Section: Introductionmentioning
confidence: 99%